Exploring individual differences in online and face-to-face help-seeking intentions in case of impending mental health problems: The role of adult attachment, perceived social support, psychological distress and self-stigma - Jennifer Apolinário-Hagen; Annina Trachsel Dugo; Lisa Anhorn; Britta Holsten; Verena Werner; Simone Krebs (Journal of Health and Social Sciences)
Background: Even though common mental health problems such as depression are a global burden calling for efficient prevention strategies, still many distressed individuals face hurdles to access public mental healthcare. Thus, computerized Internet-based psychological services have been suggested as viable approach to overcome barriers, such as self-stigma, and to inform the access to professional support on a large scale. However, little research has targeted predictors of online and face-to-face help-seeking intentions. Objective: This study aimed at determining whether associations between attachment insecurity and the willingness to seek online versus face-to-face counselling in case of impending emotional problems are mediated by both perceived social support and psychological distress and moderated by self-stigma. Methods: Data was collected from 301 adults from the German-speaking general population (age: M = 34.42, SD = 11.23; range: 18 - 65 years; 72.1% female) through an anonymous online survey. Determinants of seeking help were assessed with the self-report measures Experiences in Close Relationship-Scale, Perceived Stress Questionnaire, ENRICHD-Social Support Inventory and an adapted version of the General Help Seeking Questionnaire (i.e. case vignette). Mediation analyses were performed with the SPSS-macro PROCESS by Hayes. Results: About half of the sample indicated being not aware of online counselling. As expected, insecure attachment was associated with less perceived social support and increased psychological distress. Mediational analyses revealed negative relationships between both attachment avoidance and self-stigma with face-to-face help-seeking intentions. Moreover, the relationship between attachment anxiety and the willingness to seek face-to-face counselling was mediated by social support. In contrast, none of the predictors of online counselling was statistically significant. Conclusions: Overall, this study identified negative associations between both attachment avoidance and self-stigma with face-to-face help-seeking intentions, whereas determinants of seeking online counselling remained largely unclear. Further research is required to identify the role of e-awareness and e-mental health literacy in terms of online counselling uptake.